Relationship between zinc and cadmium contents and cultivating conditions of gourmet and medicinal mushroom Agaricus subrufescens - Jasinska, A.; Wojciechowska, E.; Stoknes, K.; Siwulski, M.; Mleczek, M.; Niedzielski , P. (International Journal of Horticultural Science, 2019)
Almoust half of the world’s population is at risk for inadequate zinc (Zn) intake, a strategic trace element that is necessary for a healthy immune system. A lack of zinc can make a person more susceptible to disease and illness. There is a need of defining additional sources of zinc in diet. Cadmium (Cd), however, and its toxicity in food chain receives considerable public and scientific attention. Cd is primarily toxic to kidney and can cause bone demineralization. In many areas in the EU, intake of Cd is not far from maximum tolerable. Mushrooms are well known for accumulating metal ions such as zinc and cadmium. Objective of this study was to define relationship between cultivation systems and conditions on zinc and cadmium content in fruit bodies of Agaricus subrufescens grown on different substrates. Cultivation was performed on mushroom composts based on increasing amount of digestate from anaerobic digestion treatment processes mixed with wheat straw and paper. The Zn and Cd concentration was defined in fruiting bodies, correlated with yield, flush and element concentration in substrates. Results showed percentage of food waste digestate and other components used in experiment had influence on concentration of Zn and Cd in mushroom compost and in A. subrufescens. Zn accumulated in collected mushrooms in amounts reaching from 42.8 to 126.9 mg kg-1 Cd content ranged 2.6 to 17.9 mg kg-1. Significant correlations for Zn concentration between mushrooms and substrates showed increase of Zn in mushrooms when cultivated on substrates with higher amount of digestate.